2010
DOI: 10.1111/j.1540-8191.2010.01100.x
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Complications of Giant Cell Arteritis: A Diagnostic and Management Dilemma

Abstract: We describe three giant cell aortitis patients who were operatively managed at our institution over the last seven years and review the recent relevant literature to highlight the specific features of the disease and the salient points of management in relation to the cardiac surgeon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In one study, follow-up at 6 months showed complete disappearance in 8.8%, improvement in 47.1%, unchanged in 41.2% and deterioration in 2.9% (72). A French study using CT scans to diagnose aortitis, also disclosed a more favorable prognosis as 10 of 11 patients achieved complete resolution or improvement at follow-up (92). Risk factors for development of large vessel vasculitis in GCA have been insufficiently investigated.…”
Section: Ophthalmologic Manifestationsmentioning
confidence: 99%
“…In one study, follow-up at 6 months showed complete disappearance in 8.8%, improvement in 47.1%, unchanged in 41.2% and deterioration in 2.9% (72). A French study using CT scans to diagnose aortitis, also disclosed a more favorable prognosis as 10 of 11 patients achieved complete resolution or improvement at follow-up (92). Risk factors for development of large vessel vasculitis in GCA have been insufficiently investigated.…”
Section: Ophthalmologic Manifestationsmentioning
confidence: 99%
“…In one study, follow-up at 6 months showed complete disappearance in 8.8%, improvement in 47.1%, unchanged in 41.2% and deterioration in 2.9% (72). A French study using CT scans to diagnose aortitis, also disclosed a more favorable prognosis as 10 of 11 patients achieved complete resolution or improvement at follow-up (92). Risk factors for development of large vessel vasculitis in GCA have been insufficiently investigated.…”
Section: Ophthalmologic Manifestationsmentioning
confidence: 99%
“…Although the inflammatory changes in the aorta of our patient were not diagnostic, after exclusion of other causes of large vessel vasculitis, we suggest that the orbital apex syndrome, pleural effuions and subsequent aortic dissection were most likely an unusual presentation of giant cell arteritis. [1][2][3][4][5] …”
mentioning
confidence: 99%